Analisis Yuridis Terhadap Perkara Perceraian Nikah Siri - Nur wahyu illahi (Tebuireng: Journal of Islamic Studies and Society, 2023)
The subject raised in this thesis is the existence of a secret marriage but filing for divorce in the Religious Court. The judge uses Article 7 paragraph (3) letter a of the Islamic Law Compilation as a consideration to prove the marriage. This research analyzes the case number 7073/Pdt.G/2021/PA.Kab.Mlg regarding the consolidation of proving marriage and divorce according to positive law in Indonesia. The research method used is empirical research method through interviews and observations at the District Court of Malang with descriptive, evaluative, and prescriptive data analysis. The researcher analyzes the verdict number 7073/Pdt.Kab.G/2021/PA.Mlg using the Legal Ethical Theory, which indicates that the use of Article 7 (3) letter (a) of the Islamic Law Compilation is questionable in terms of legal interpretation when compared to applicable laws and regulations. However, despite this, the case remains valid, but legal certainty in case administration cannot be achieved.